Psychosocial effects of social media on the Saudi society during the Coronavirus Disease 2019 pandemic: A cross-sectional study. - Mohammad Ahmed Hammad; Turki Mahdi Alqarni (PLoS ONE)
The Coronavirus Disease 2019 (COVID-19) pandemic has been posing a substantial challenge to human survival and well-being, which rely on the actions and behaviors of individuals. It is essential that accurate information is distributed; however, misinformation has been spread via social media. Consequently, the resulting panic has to be addressed while putting essential public health measures in place. It is also important to explore the link between the social media exposure and well-being. Therefore, in the current study, we aimed to identify the levels of anxiety, depression, and social isolation among individuals during the COVID-19 pandemic. Additionally, we explored the relationship between exposure to misleading social media news and anxiety, depression, and social isolation. A cross sectional design was employed to collect data from 371 Saudi participants (aged 16-60 years), using the Generalized Anxiety Disorder-7, Centre for Epidemiological Studies Depression Scale, and de Jong Gierveld Loneliness Scale. Results showed that the prevalence of anxiety, depression, and social isolation was 47.82%, 47.57%, and 46.42%, respectively. Further, more than 83% of the participants reported using social media frequently during the pandemic. We found that exposure to misinformation via social media has a significant positive relationship with anxiety, depression, and social isolation. However, Due to the cross-sectional nature of this study it cannot be determined whether social media causes negative mental health outcomes, or if individuals experiencing greater depression, anxiety and social isolation turn to social media more than others, or if some third variable might explain both. Based on our findings, we present specific suggestions related to the COVID-19 pandemic to the government of Saudi Arabia. Minoring and filtering out misleading information with the cooperation of the World Health Organization (WHO) can promote the spread of accurate news in Saudi Arabia.